Biodegradation and Micro- Scale Treatability Pattern of Loblolly Pine Heartwood Bioincised by Bacillus Subtilis and Physisporinus Vitreus - Ismaeil Zahedi Tajrishi (University of Zagreb, Faculty of Forestry and Wood Technology, 2021)
One strategy for improving the treatability of refractory wood species is biological incising, and its efficiency depends on how the microorganisms modify the porous structure of the wood. Evaluation of the bioincised wood treatability on a micro-scale can thus help to better understand the treatability enhancing mechanisms. In the present study, the biodegradation pattern and micro-scale treatability of Loblolly pine (Pinus taeda L.) heartwood were determined after bioincising with the white-rot fungus Physisporinus vitreus (Pers.: Fr.) P. Karsten isolate 136 and bacterium Bacillus subtilis UTB22. Oven-dried specimens with dimensions of 50 mm × 25 mm × 15 mm (L × T × R) were incubated with the microorganisms at (23±2) °C and (65±5) % relative humidity for six weeks. The control and exposed wood blocks were then pressure treated by 1 % fluorescent dye (fluorescein)-containing water to study the treatability pattern under a fluorescence microscope. The longitudinal and tangential air permeability and compression strength parallel to the grain of the specimens were also determined at the end of the incubation period. Scanning electron microscopic (SEM) studies showed that degradation by B. subtilis UTB22 was limited to the pit membranes, but the cell walls were also degraded to some extent by P. vitreus. The fungus caused a higher mass loss compared to the bacterium, whereas the permeability enhancing ability of the bacterium was more pronounced. The fluorescent dye tracer also showed that higher treatability with more uniformity was obtained by B. subtilis UTB22. The improvement in treatability by both microorganisms was mainly due to the degradation of the earlywood tracheids.